2010
DOI: 10.1177/0011000010378449
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Objectification and Substance Abuse in Young Adult Women

Abstract: Objectification Theory (Fredrickson & Roberts, 1997) provides an important perspective for understanding the experiences of women living in a culture that sexualizes and objectifies the female body. The purpose of this study was to examine the relationships between interpersonal sexual objectification experiences and women’s substance abuse in a sample of 289 young adult women. Findings indicate that both everyday (e.g., body evaluation) and extreme (i.e., sexual victimization) forms of sexual objectificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 80 publications
5
61
1
Order By: Relevance
“…Second, no control variables were measured in Study 1, so factors that co-occur with both trait body shame and poor health may explain the results. For example, trait body shame is linked to depression (e.g., Grabe et al, 2007), smoking (Carr & Szymanski, 2010;Fiissel & Lafreniere, 2006), and body mass index (BMI; Calogero, 2004). Because these factors are also linked to immune dysregulation (e.g., Falagas & Kompoti, 2006;KiecoltGlaser & Glaser, 2002;Nuorti et al, 2000), poor self-rated health (e.g., Han, 2002;Manderbacka et al, 1999;Okosun et al, 2001), and symptoms (e.g., Goldberg et al, 2000;Janke et al, 2007;Krebs et al, 2008), they may account for trait body shame's observed effects on health outcomes.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…Second, no control variables were measured in Study 1, so factors that co-occur with both trait body shame and poor health may explain the results. For example, trait body shame is linked to depression (e.g., Grabe et al, 2007), smoking (Carr & Szymanski, 2010;Fiissel & Lafreniere, 2006), and body mass index (BMI; Calogero, 2004). Because these factors are also linked to immune dysregulation (e.g., Falagas & Kompoti, 2006;KiecoltGlaser & Glaser, 2002;Nuorti et al, 2000), poor self-rated health (e.g., Han, 2002;Manderbacka et al, 1999;Okosun et al, 2001), and symptoms (e.g., Goldberg et al, 2000;Janke et al, 2007;Krebs et al, 2008), they may account for trait body shame's observed effects on health outcomes.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…Moreover, body shame has been linked to more severe clinical outcomes including disordered eating (Calogero, 2009;Tylka & Hill, 2004), depression (Grabe, Hyde, & Lindberg, 2007;Szymanski & Henning, 2007), sexual dysfunction (Calogero & Thompson, 2009;Sanchez & Kiefer, 2007), and substance abuse (Carr & Szymanski, 2011). In addition, shame has been linked to experiences of both SV and IPV (Rhatigan, Shorey, & Nathanson, 2011;Sable, Danis, Mauzy, & Gallagher, 2006;Spangaro, Zwi, & Poulos, 2011;Walker, 1984Walker, , 2000Walker, , 2009.…”
Section: Objectification Theorymentioning
confidence: 99%
“…Of the few studies that have considered the links between SV and these body image-related variables, most are consistent with the notion that SV is positively associated with self-objectification, body surveillance, and body shame. In their study investigating substance abuse in relation to sexual objectification, Carr and Szymanski (2011), for example, also assessed whether college women's reported frequency of everyday sexual objectification experiences, including body evaluation and unwanted explicit sexual advances, and extreme sexual objectification experiences, including sexual assault, were related to body surveillance and body shame. Consistent with objectification theory, body evaluation, unwanted explicit sexual advances, and sexual assault were each positively associated with both body surveillance and body shame.…”
Section: Objectification Theorymentioning
confidence: 99%
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%